2013 IX Internatioal Conference on Antenna Theory and Techniques 2013
DOI: 10.1109/icatt.2013.6650826
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites for antenna-feeder systems

Abstract: The paper presents results of study of frequency dependence of permittivity and permeability of composite materials based on various polymer matrices and fillers in the form of nanoscale powders -nanoparticles of Si, carbon nanotubes, and magnetite nanoparticles. It is shown that, using the nanodisperse electrically conducting fillers, it is possible to obtain materials with the required dielectric permittivity, and in the case of magnetic nanoparticles to obtain materials with the appropriate magnetic propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The BW of the DRA's was verified in À10 dB in the return loss graph, where it was observed that the variation of the content of magnetic nanoparticles did not cause any considerable alterations. The use of magnetite in nanocomposites for antenna-feeder systems is very desirable, once according to literature [49] magnetic nanoparticles allow to process materials with the suitable magnetic properties.…”
Section: Application Of the Nano-biocomposites As Dielectric Resonatomentioning
confidence: 99%
“…The BW of the DRA's was verified in À10 dB in the return loss graph, where it was observed that the variation of the content of magnetic nanoparticles did not cause any considerable alterations. The use of magnetite in nanocomposites for antenna-feeder systems is very desirable, once according to literature [49] magnetic nanoparticles allow to process materials with the suitable magnetic properties.…”
Section: Application Of the Nano-biocomposites As Dielectric Resonatomentioning
confidence: 99%
“…In this work, using a frequency range of 0.4-4.5 GHz, dipolar orientation is the predominant mechanism of dielectric polarization and the greatest reduction in ε values for BC-based composites suggests the lower mobility of the BC matrix in comparison to Ch and Col, as well as the dielectric relaxation process being related to the increase in tan δ values. Figure 6d shows the variation of ε at 4.45 GHz with SPIONs content (0, 30, 50 and 80% w/w) in the matrix, which showed the dielectric property increasing by SPION increments into composite films, as recorded by Bibikov et al (2013) [53]. Chemically, the resistive ceramic structure of Fe 3 O 4 @bPEI NPs positively contributes to higher ε values due to polar amine groups from bPEI molecules.…”
Section: Microwave Dielectric Spectroscopymentioning
confidence: 94%